PENGARUH KEBIASAAN BELAJAR DAN KEMAMPUAN NUMERIK TERHADAP PRESTASI BELAJAR MATEMATIKA - Lin Mas Eva (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2019)
The study aims to determine the extent of the influence of Learning Habits and Numerical Ability on Mathematics Learning Achievement. the research was conducted by survey method. The population of this study was the seventh grade students of North Cikarang North SMP with a sample size of 40 students, with the sampling technique used was simple random sampling. The results of testing the hypothesis obtained conclusions as follows: 1) There is a significant influence between learning habits and numerical abilities together on mathematics learning achievement. 2) There is a significant influence between learning habits and mathematics learning achievement, and 3) There is a significant influence between numerical abilities and mathematics learning achievement.